The case for embedding researchers in conservation agencies. Issue 6 (22nd May 2019) - Roux, Dirk J.; Kingsford, Richard T.; Cook, Carly N.; Carruthers, Jane; Dickson, Katrina; Hockings, Marc
Abstract: Although protected areas represent a pivotal response to escalating anthropogenic threats, they face many pressures, inside and outside their boundaries. Amid these challenges, effective conservation is guided by evidence‐based decision making supported by dynamic processes of learning and knowledge exchange. Although different models promote knowledge exchange, embedding research scientists within conservation agencies is best suited to supporting evidence‐based conservation. Based on available literature and our experiences on several continents, we considered the benefits, challenges, and opportunities associated with embedding research scientists within conservation agencies and the research required to better understand the effectiveness of the embedding model for evidence‐based conservation. Embedded researchers provide long‐term commitment to building social capital among academic and nonacademic stakeholders; act as skilled gatekeepers who increase 2‐way flow of knowledge between scientists and managers; attract, coordinate, and support management‐relevant external research projects; drive the design and maintenance of long‐term monitoring; and align their research with information needs. Notwithstanding the many benefits, research capacity of conservation agencies is declining worldwide. A significant challenge is that the values, structures, functions, and effectiveness of the embedding model of knowledge exchange remain poorly evaluated and documented. Also, embedded researchers have to balance their desire for creativity and flexibility with the standardization and quality control required by their public sector agencies; may be perceived as not credible because they are not truly independent of their agency; and have to couple scientific productivity with skills for transdisciplinary research, social facilitation, and stakeholder engagement. Systematic research on embedding and other models of knowledge exchange, across different world contexts, is required to better understand the benefits, costs, and institutional arrangements associated with different models. Abstract : Article impact statement : Embedding researchers in conservation agencies can promote knowledge exchange, research relevance, and management effectiveness. Abstract : El Caso para la Incorporación de Investigadores en las Agencias de Conservación Resumen: Aunque las áreas protegidas representan una respuesta crucial a las crecientes amenazas antropogénicas, estas enfrentan muchas presiones dentro y fuera de sus fronteras. En medio de estos desafíos, la conservación efectiva se guía por la toma de decisiones con base en evidencias respaldada por los procesos dinámicos de aprendizaje e intercambio de conocimiento. Mientras que diferentes modelos promueven el intercambio de conocimiento, la incorporación de investigadores científicos en las agencias de conservación es más adecuada para respaldar la conservación basada en evidencias. Con base en la literatura disponible y en nuestras experiencias en varios continentes consideramos los beneficios, desafíos y oportunidades asociadas con la incorporación de investigadores científicos en las agencias de conservación y la investigación requerida para entender de mejor manera la efectividad del modelo de incorporación para la conservación basada en evidencias. Los investigadores incorporados proporcionan un compromiso a largo plazo con la construcción de un capital social entre los accionistas académicos y no académicos; fungen como guardianes habilidosos que incrementan el flujo de dos vías de conocimiento entre los científicos y los administradores; atraen, coordinan y apoyan los proyectos de investigación externos relevantes para el manejo; llevan el diseño y el mantenimiento del monitoreo a largo plazo; y alinean su investigación con las necesidades de información. A pesar de los beneficios, la capacidad de investigación de las agencias de conservación está declinando a nivel mundial. Un desafío significativo es que los valores, estructuras, funciones y efectividad del modelo de incorporación del intercambio de conocimiento permanecen pobremente evaluados y documentados. Además, los investigadores incorporados tienen que balancear su deseo por ser creativos y flexibles con la estandarización y el control de calidad requeridos por sus agencias del sector público; pueden ser percibidos como no creíbles porque no son realmente independientes de su agencia; y tienen que emparejar la productividad científica con las habilidades de investigación transdisciplinaria, facilitación social y participación de los accionistas. Se requiere de la investigación sistemática sobre la incorporación y otros modelos de intercambio de conocimiento en diferentes contextos globales para entender de mejor manera los beneficios, costos y arreglos institucionales asociados con diferentes modelos. 摘要: 保护地在当前人为威胁不断升级的现状下对保护起着关键作用, 然而, 在保护地的边界内外都面临着许多压力。为应对这些压力和挑战, 需要那些被动态学习过程和知识交换支持的基于证据的决策来指导有效保护。尽管许多不同的模式都可以促进知识交换, 但在保护机构中吸纳科学家的做法才最能支持基于证据的保护。根据现有的文献和我们在多个大洲的经验, 我们探讨了将研究者纳入保护机构的好处、挑战和机遇, 以及为了更好地理解吸纳研究者的模式对基于证据的保护的有效性仍需进行的研究。加入保护机构的研究者会长期致力于建立学术界和非学术界的利益相关者之间的社会资本; 担当把关人来增加科学家和管理者之间的双向知识交流; 吸引、协调和支持与管理相关的外部研究项目; 推动长期监测项目的设计和维护; 并根据信息需求来进行他们的研究。虽然这样做有许多好处, 但世界范围内, 保护机构的研究能力却正在下降。目前面临的一个重要挑战在于, 这种人才吸纳式的知识交换模式的价值、结构、功能和有效性仍然没有得到很好的评估和记录。此外, 研究者必须在对创造力和灵活性的渴望与公共部门机构要求的标准化和质量控制之间取得平衡, 可能会因为并非完全独立于他们的服务机构而被认为不可信; 还必须将科学生产力与跨学科研究、社会促进和推动利益相关者参与等技能相结合。为了更好地理解各种知识交换模式的利益、成本和制度安排, 未来需要对不同领域背景下的人才吸纳及其它模式进行系统性的研究。【翻译: 胡怡思; 审校: 聂永刚】